Athletic identity, anxiety, and depression in moderate to highly specialized female adolescent volleyball players - Clark, V. Claire; Ulman, Sophia M.; Erdman, Ashley L.; Gale, Emily B.; Janosky, Joseph; Stapleton, Emily J. (Frontiers in Psychology, 2025)
IntroductionIndividuals strongly tied to their athletic sense of self, athletic identity, may have increased sport specialization and behaviors elevating injury risk, overtraining, and mental health concerns. No known studies have explored the relationship between athletic identity, specialization, and youth athletes’ mental health concerns, specifically anxiety and depression. This study assessed the relationship between athletic identity, specialization, and mental health symptoms among female, high school athletes.MethodsAthletic identity and mental health were assessed via the Athletic Identity Measurement Scale (AIMS) and Revised Children’s Anxiety and Depression Scale (RCADS). A sport participation survey recorded injury history, specialization, and training volume. Mann -Whitney U tests compared RCADS scores between high athletic identity (>54 total AIMS) and low athletic identity (<55 total AIMS; α = 0.05) athletes.ResultsA total of 149 female volleyball athletes were included (16.0 ± 0.9 years), with 54.4% (81/149) classified as high athletic identity. Injury rates did not significantly differ between high and low athletic identity groups. Highly specialized athletes differed on multiple RCADS subscales, with high athletic identity correlated with greater separation anxiety (p = 0.012), generalized anxiety (p = 0.006), social phobia (p = 0.020), depression (p = 0.011), total anxiety (p = 0.005), and total anxiety and depression (p = 0.002). The moderately specialized group did not differ in RCADS scores between high and low athletic identity athletes.DiscussionThose with high athletic identity practiced more and had more anxiety and depressive symptoms than those with low athletic identity but were not at higher injury risk for injury. Providers should consider routine mental health screenings for high athletic identity athletes and promote psychoeducation on the importance of developing coping skills and diverse interests outside of one’s primary sport.